EL DERECHO A LA EDUCACIÓN EN COLOMBIA, DESDE LA PERSPECTIVA DE LOS DERECHOS HUMANOS (2016)
This article aims to make a thoughtful analysis of the right to education in Colombia, from the perspective of human rights. The descriptive analytical methodology is implemented using as sources of information pronouncements of the Constitutional Court, international conventions, rules, articles housed research results in specialized databases and books. the issue is approached from the perspectives of human and fundamental right as well as from the constitutional and legal regulatory framework; concludes that while progress has been made in the regulatory adjustment to ensure the right to education in Colombia this is still slow and inefficient in terms of the demands of the country; however it for the satisfaction of the right to free and compulsory primary education, it is urgent that effective implementation of international standards and repeated recommendations of the organs of protection of human rights are met. In addition, it is necessary that the case law that, in education, has developed abide by the Constitutional Court.